(untitled) (Sains Humanika, 2021)
Quality of Work Life is important for companies to employ quality workers and for workers it can be useful to ensure their welfare, have a good working climate and conditions and ultimately have a personal psychological impact on each worker. Therefore, in the 5.0 era, which requires that we be able to use modern-based science (AI, robots, IoT) to serve human needs in order to create a society that enjoys life and feels comfortable. The purpose of this research is to present comparisons so that readers can enrich their understanding of quality. working life. The conclusion that influences the quality of work life in 15 (fifteen) journals that have been reviewed dominantly is seen in 9 (nine) factors from Cascio’s opinion and 12 (twelve) factors from Chandranshu Sinha’s opinion. In the era of society 5.0, a differentiation strategy is also needed, namely an organizational strategy that aims to produce a product or service that is different from the products or services of other companies. Human resources with good quality of work life will easily implement a differentiation strategy because the factors that influence it coupled with the use of advanced technology that are developing will advance the industry in a country.